An exploration of the clinical learning experience of nursing students in nine European countries - Warne, Tony; Johansson, Unn-Britt; Tichelaar, Erna; Tomietto, Marco; Bossche, Koen Van den; Morenog, Maria Flores Vizcaya; Saarikoski, Mikko; Papastavrou, Evridiki (My University, 2010)
The overall aim of the study was to develop a composite and comparative view of what factors enhance the learning experiences of student nurses whilst they are in clinical practice. The study involved students undertaking general nurse training programmes in nine Western European countries. The study focused on: (1) student nurse experiences of clinical learning environments, (2) the supervision provided by qualified nurses in clinical placements, and (3) the level of interaction between student and nurse teachers. The study utilised a validated theoretical model: the Clinical Learning Environment, Supervision and Nurse Teacher (CLES. +. T) evaluation scale. The evaluation scale has a number of sub-dimensions: Pedagogical atmosphere on the ward; Supervisory Relationships; the Leadership Style of Ward Managers; Premises of Nursing; and the Role of the Nurse Teacher. Data (N= 1903) was collected from Cyprus, Belgium, England, Finland, Ireland, Italy, Netherlands, Spain and Sweden using web-based questionnaire 2007-2008. The findings revealed that respondents were generally satisfied with their clinical placements. There was clear support for the mentorship approach; 57% of respondents had a successful mentorship experience although some 18% of respondents experienced unsuccessful supervision. The most satisfied students studied at a university college, and had at least a seven week clinical placement supported by individualised mentorship relationships. Learning to become a nurse is a multidimensional process that requires both significant time being spent working with patients and a supportive supervisory relationship.
Keywords: Clinical placements; Mentorship; Nurse education; Professional development